A Study on the Students’ Attitude in English Summative and Formative Assesment at the Eighth Grade Students of MTs Hubbulathan Duri (International Journal of Business and Information Technology, 2022)
Based on the researcher observation, it was found that most of the students have difficulties in finding factual information of the text. The major problem faced by them was found have difficulties in finding the main idea of the text, So the writer was interested in carrying out the research about this problem. The objective of the research is to find out Students’ reading comprehension before taught by using Mental imagery strategy to find out students’ reading comprehension after taught by using Mental imagery strategy and to find out significant effect of using Mental imagery strategy toward Students’ reading comprehension. The design of this research was Pre-Experimental. There are 6 class in SMP IT Mutiara Duri. The Population the eighth grade student in SMP IT Mutiara Duri is 181 students. The researcher will use one class, VIII.Syukur (31 students) as sample. The writer gave pre-test to experimental class. Then, the writer gave treatment for experimental class. Finally, the writer gave post-test to experimental class in order to know the effectiveness of Mental imagery strategy that applied by the writer. The technique of collecting data was the test. The technique of analyzing data, the writer adopted paired sample t-test formula by using software SPSS V.17. After analyzing the data, the writer found that there is a significant effect of using Mental imagery strategy toward Students’ reading comprehension at SMP IT Mutiara Duri.